Peningkatan Kemampuan Menulis Teks Tanggapan Melalui Strategi Menulis Terbimbing Berbantuan Lagu 'Masih Ada Waktunya' Pada Murid Kelas 7c Smpn 17 Malang - Syaharani Setyo Prameswari; Wadji Wadji; Chusnaini Chusnaini (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPROVING THE ABILITY TO WRITE RESPONSE TEXTS THROUGH GUIDED WRITING STRATEGIES HELPED BY THE SONG 'STILL THERE'S TIME' IN CLASS 7C STUDENTS OF SMPN 17 MALANG IN THE 2025/2026 ACADEMIC YEAR The reasons for the low ability to write response texts of seventh-grade students at SMPN 17 Malang include traditional learning methods, limited sources of inspiration, and a lack of creative ideas, which cause boredom and laziness. This classroom action research (CAR) aims to improve students' ability to write response texts by implementing a Guided Writing Strategy (SMT) with the source of inspiration from the song "Masih Ada Waktunya" sung by Nadhif Basalamah. This research was conducted in two cycles with 27 students. Research data were collected through learning outcome tests and activity observations, then analyzed descriptively comparatively. The results showed a significant increase in students' writing abilities. The average grade in the class increased from 66 in the pre-cycle phase to 77 in cycle 1 and 89 in cycle 2. In addition, the percentage of student completion also increased. If in the previous phase it was only 41%, this figure increased to 78% in cycle I and reached an optimal value of 89% in cycle II. It can be said that the guided writing strategy assisted by the song "Masih Ada Waktunya" is effective in improving students' independent learning outcomes in providing feedback through intensive individual guidance.